Uji Sensitivitas Ekstrak Kasar Batang Ciplukan (Physalis angulata) Terhadap Bakteri Pseudomonas fluorescens Secarain Vitro - Ion Tarsardo Sianturi; Arief Prajitno; Ellana Sanoesi (Faculty of Science and Technology University Ibrahimy, 2019)
Diseases is a problem in aquaculture, one of which is the diseases caused by the bacteriumP.fluorescens. Antibiotics and chemicals materials themselves can give the bacterium resistance and cause harm for the environment. One alternative that can be done is using a natural material, namely the rod of ciplukan (p. angulata). The purpose of this research was to explain the effect of P. angulata on the growth of p. fluorescens. The method which can be use is experimental method by using the research design of completely randomized design (ral) with 5 treatment and 2 control with 3 repetitions. The results showed that extract of P. angulata at various dose (6,67 ppt, 13,33 ppt, 19,99 ppt, 26,66 ppt and 33,33 ppt) exhibited anti-P. fluorescens activity with inhibition zone diameters in the range of (4,06±0,07 mm - 9,63±1,61 mm). Increashing extract dose lead to increased the inhibition zone. The extract dose of 33,33 ppt exhibited best anti-P. fluorescens activity in this research. The research results show that P. angulata is proven to be able to inhibit the P. fluorescens, but to prove the effectiveness of this material, an in vivo is required.